2009
DOI: 10.1111/j.1349-7006.2009.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma‐associated antigens recognized by tumor‐infiltrating B cells and the clinical significance of the antibody titers

Abstract: Malignant pleural mesothelioma (MPM) is difficult to diagnose at an early stage. The present study attempted to obtain a tumor-specific antibody against MPM derived from tumor-infiltrating B lymphocytes in MPM by using a xenotransplanted severe combined immunodeficiency (SCID) mouse model, and to identify the antigens recognized by the antibodies. Among the antigen-antibody relationships, the clinical usefulness of antibody titers in the sera was evaluated from the viewpoint of diagnosis of MPM and monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…A real-time quantitative RT-PCR assay was performed with FastStart Essential DNA Green Master (Roche Applied Science, Indianapolis, IN, USA) and the LightCycler Nano (Roche Diagnostics, Mannheim, Germany). Primers for the PCR of β-actin, COX-2, and CHIP were taken from previous studies (Wu et al, 2003;Shigematsu et al, 2009;Roelofs et al, 2014). The reaction conditions for COX-2 were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 58°C for 10 sec, and 72°C for 15 sec, and for CHIP were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 60°C for 10 sec, and 72°C for 15 sec.…”
Section: Analysis Of Reverse Transcription-polymerase Chain Reaction mentioning
confidence: 99%
“…A real-time quantitative RT-PCR assay was performed with FastStart Essential DNA Green Master (Roche Applied Science, Indianapolis, IN, USA) and the LightCycler Nano (Roche Diagnostics, Mannheim, Germany). Primers for the PCR of β-actin, COX-2, and CHIP were taken from previous studies (Wu et al, 2003;Shigematsu et al, 2009;Roelofs et al, 2014). The reaction conditions for COX-2 were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 58°C for 10 sec, and 72°C for 15 sec, and for CHIP were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 60°C for 10 sec, and 72°C for 15 sec.…”
Section: Analysis Of Reverse Transcription-polymerase Chain Reaction mentioning
confidence: 99%
“…As we have shown what seems to be an opposing effect of the same inflammatory response depending on the location, the findings of CD8 + T cells need further exploration with specific focus on location. Shigematsu et al [23] also found that tumor-infiltrating B cells recognize mesothelioma-associated antigens in murine models. The clinical significance of B cells has not been investigated in human MPM tumors.…”
Section: Discussionmentioning
confidence: 99%
“…THBS2 has been found overexpressed in 3 independent transcriptome studies on mesothelioma tissues (10) and, previously, the titers of the antibody against THBS2 has been proposed as a tumor marker for the diagnosis and follow up of patients with MPM. THBS2 antibody has been detected in the 88.9% of the mesothelioma patients sera analysed and interestingly, the serum antibody titers decreased after surgical treatment of MPM and increased after recurrence of the disease (76).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%